Dual-redox enhanced supercapacitors with sodium anthraquinone-2-sulfonate and potassium bromide. (1st April 2021) - Miao, Xiaofei; Zhang, Xiangxin; Chen, Sujing; Liu, Yongchuan; Chen, Yuanqiang; Lin, Junhong; Chen, Qi; Zhang, Yining
Highlights: AQS-KBr dual-redox couples system is introduced in to carbon-based supercapacitors for performance enhancement. The negative and positive electrodes are enhanced by AQS and KBr, respectively. The optimum adsorption of AQS is determined through systematic testing. The optimum concentration of KBr is determined through capacity matching with the enhanced negative electrode. The AQS-KBr enhanced-supercapacitor has no attenuation during 10000 cycles at 2 A g −1 . Abstract: For improving the energy density of carbon-based supercapacitors, the highly reversible redox mediators with giant pseudocapacitance have been studied extensively. In this work, the dual-redox combination of sodium anthraquinone-2-sulfonate (AQS) and potassium bromide (KBr) is introduced into the carbon-based supercapacitors to enhance the electrochemical performances. In the dual-redox enhanced supercapacitors (DRESc), the performances of negative and positive electrodes are improved by AQS and KBr, respectively. In order to use AQS and KBr rationally and effectively, two different approaches are studied: (I) redox mediators are adsorbed in the electrodes; (II) redox mediators are added into the electrolyte. The experimental results demonstrate that the combination of adsorbing AQS onto the negative electrode (the approach I) and adding KBr in the electrolyte (the approach II) is the best approach. Furthermore, electrochemical results prove that it is an optimal choice to adsorb 3 mg AQS for the negative electrode in this work. Meanwhile, to match the AQS-enhanced negative electrode, synchronous potential measurements indicate that the optimal choice for the positive electrode is adding 1.5 M KBr in the 1 M H2 SO4 electrolyte. Finally, the DRESc achieved a maximum gravimetric energy density (EG ) of 32.05 Wh kg −1 at 0.5 A g −1 and a maximum gravimetric power density (PG ) of 2200 W kg −1 at 8 A g −1, implying that the AQS-Br dual-redox system is a promising candidate for energy storage and conversion. Graphical abstract: Image, graphical abstract